PENGEMBANGAN MEDIA PEMBELAJARAN FIQIH DI ERA MODERN - Vera Susanti; Achmad Syarifudin; Rubi Awalia; Umi Nasikhah (CV. ADIBA AISHA AMIRA, 2026)
The development of information and communication technology in the modern era has had a significant impact on the world of education, including the teaching of fiqh. Fiqh teaching materials have become a key component in enhancing students’ understanding of the concepts of worship, ethics and Islamic law in a more interactive and engaging manner. The development of fiqh learning media is not limited to textbooks but also encompasses the use of digital media, images, videos, and animations capable of capturing students’ attention and facilitating teachers in delivering the material. This study discusses various strategies for developing fiqh learning media relevant to students’ needs in the modern era, such as the utilisation of interactive multimedia, educational games, and technology-based learning applications. The results indicate that the use of innovative learning media can enhance students’ motivation to learn, their understanding of the material, and their active participation. Furthermore, creatively developed media also encourages teachers to apply more varied and contextual teaching methods, thereby making the fiqh learning process more effective and enjoyable.